Assessing regional key sectors in Italy: A comparative approach - Gustav Schachter; Tullio Gregori (European Regional Science Association (ERSA), 1998)
The paper attempts to assess the impact of public policies on closing the regional gap between regions in Italy. In the 1990's Italian Southern regions occupy the same position within the nation that they held in 1951. Since the fifities an array of public policies has been devised and partially implemented to close the gap with no avail. Here we are concerned with public policies that can increase production and employment. Using regional Input/Output table for 1985, we try to determine whether a better allocation of public funds can increase output and underutilized resources. For this task we adopt standard and non standard techniques, such as structural path analysis, block analysis and graph theory, to devise more propulsive sectors and more important links between industries.
Keywords: 330